2017
DOI: 10.1186/s13034-017-0180-5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s mental health problems and their relation to parental stress in foster mothers and fathers

Abstract: BackgroundThis study focuses on children living in foster families with a history of maltreatment or neglect. These children often show adverse mental health outcomes reflected in increased externalizing and internalizing problems. It is expected that these adverse outcomes are associated with increased parental stress levels experienced by foster mothers as well as foster fathers.MethodsThe study sample included 79 children living in foster families and 140 children living in biological families as comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 28 publications
1
36
1
3
Order By: Relevance
“…One mechanism is mental health symptoms as a result of parenting stress (Duca, 2015;Gerstein, Crnic, Blacher, & Baker, 2009;Kim, Dababnah, & Lee, 2019 stress (Hayes & Watson, 2013;Theule, Wiener, Tannock, & Jenkins, 2013). This heightened stress level originates from the burden of care, isolation, and educational challenges associated with their parenting role (Anderson, 2008;Lohaus et al, 2017;Mofokeng & van der Wath, 2017).…”
Section: Parent's Mental Health May Underpin Family Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…One mechanism is mental health symptoms as a result of parenting stress (Duca, 2015;Gerstein, Crnic, Blacher, & Baker, 2009;Kim, Dababnah, & Lee, 2019 stress (Hayes & Watson, 2013;Theule, Wiener, Tannock, & Jenkins, 2013). This heightened stress level originates from the burden of care, isolation, and educational challenges associated with their parenting role (Anderson, 2008;Lohaus et al, 2017;Mofokeng & van der Wath, 2017).…”
Section: Parent's Mental Health May Underpin Family Resiliencementioning
confidence: 99%
“…Increased parent mental health symptoms are associated with ineffective parenting practices as stress impairs parent's ability to cope with adversity, including challenging child behavior problems (Lohaus et al, 2017). Further, when children are perceived as more challenging to care for, parents are less likely to express their anger and frustration to others and more likely to suppress these negative emotions (Le & Impett, 2016).…”
Section: Parent's Mental Health May Underpin Family Resiliencementioning
confidence: 99%
“…1,2 Rates of problem behavior are particularly elevated in children in foster care. 3,4,5 Importantly, problem behavior in early childhood has been linked to subsequent negative outcomes, such as school failure, juvenile justice involvement, long-term physical and mental health problems, and alcohol and substance use. 5,6,7 However, while there is increased likelihood of problem behavior among children in foster care, not all of these children show clinically significant levels of problem behavior, highlighting the importance of studying individual variability in the adaptation to early adversity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, higher levels of parenting stress in foster caregivers have been associated with negative child outcomes, including alterations in the stress-response system and increased problem behavior. 3,15 Similarly, foster caregivers' implementation of consistent family routines has been linked to decreased child problem behavior and improved family well-being. 16,17 Finally, research on the discipline practices of foster caregivers has shown that lower levels of harsh discipline is associated with more positive adjustment in children in foster care, and conversely, higher levels of harsh discipline is related to increased child aggression.…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity is understood to be a "double-edged sword" (National Scientific Council on the Developing Child, 2007): while exposure to chronic stress during early childhood can have lasting influences, high-quality parenting can provide children with a foundation for healthy development (Fisher et al, 2016). Sources of stress within families are broad, including poverty, mental illness, parents' own exposure to adverse childhood experiences, a lack of perceived social support, and children's behaviour problems (Lohaus et al, 2017;Mcewen & Mcewen, 2017;Steele et al, 2016).…”
Section: Introductionmentioning
confidence: 99%